Occurrence and distribution of sucrose-metabolizing enzymes in oral streptococci. - Chassy, B M (1976)
Specific growth rates, growth yields, and the level and cellular distribution of three sucrose-metabolizing enzyme activities were determined for seven oral streptococci (Streptococcus mutans strains E49, BHT, 10449, SL-1, and LM-7, S. sanguis 10558, and S. salivarius 25975). Cultures were grown in a fermentor at pH 6 with either 20 mM glucose or 10 mM sucrose.Generation times varied between 21 and 70 min. Whereas some strains grew 10 to 50% more slowly with sucrose than with glucose, others did not. Growth was always logarithmic, and the growth yields were similar. Glcosyl transferase (EC 2.4.1.5) was largely extracellular; in sucrose cultures it was appreciably lower, but no major shift to a cell-associated form was found. In glucose cultures, the activity varied between 4 and 140 IU per 6-liter culture. The glucan formed was mostly or exclusively water insoluble. Glcosyl transferase was stimulated weakly (60% or less) by various dextrans. Fructosyl transferase (EC 2.4.1.10) was primarily extracellular (except in glucose cultures of S. salivarius) and varied between 0 and 337 IU/culture. In S. salivarius, the extracellular fructosyl transferase was induced by sucrose. In all S. Mutans cultures, the total fructosyl transferase activity was lower after growth with sucrose. All strains had extra- and intracellular invertase (EC 3.2.1.26) activity. Total levels varied between 210 and 3,500 IU/culture. Less extracellular activity was present in sucrose cultures. Only S. salivarius had appreciable activity in the cellular particulate fraction. Invertase activity was significantly higher than the combined glucosyl and fructosyl transferase activities in all cultures.